Morphofunctional and motor characteristics of Baikal region's students (Russia) with overweight - M.M. Kolokoltsev; S.S. Iermakov (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose : to study the morphofunctional and motor characteristics of the organism of students with overweight and obesity. To compare these data with data of students with normal weight. Participants : it was examined students (females - n=1937; males - n=1302) of 17-21 year-olds. (Baikal region, Russia). It was performed an anthropometrical and physiometric examination of students. It was determined the content of muscle and fat mass in the component structure of a body. It was determined the motor qualities of students. Results : the indicators of anthropometrical and physiometric characteristics, results of motor action tests, the content of muscle and fat mass in a body of students with overweight and obesity are lower in comparison with the indicators of females and males with normal body weight (р<0.05). The integral criterion of physical fitness of students with overweight and obesity is lower in comparison with students with normal body weight (р<0.05). It is defined the direct dependence between the decrease in the level of physical fitness and increase in body weight of males and females. It was obtained data concerning interrelation of anthropometrical and functional characteristics with motor qualities of males and females with different body weight. Conclusions : Results of the research allow correcting physical training classes of youth. Such classes are focused on the differentiated decrease in fat mass content and increase in muscle mass in the component structure of students' bodies.